Reversibly immortalized human umbilical cord–derived mesenchymal stem cells (UC‐MSCs) are responsive to BMP9‐induced osteogenic and adipogenic differentiation. Issue 11 (4th August 2018) - Shu, Yi; Yang, Chao; Ji, Xiaojuan; Zhang, Linghuan; Bi, Yang; Yang, Ke; Gong, Mengjia; Liu, Xing; Guo, Qi; Su, Yuxi; Qu, Xiangyang; Nan, Guoxin; et al.
Abstract: Human mesenchymal stem cells (MSCs) are a heterogeneous subset of nonhematopoietic multipotent stromal stem cells and can differentiate into mesodermal lineage, such as adipocytes, osteocytes, and chondrocytes, as well as ectodermal and endodermal lineages. Human umbilical cord (UC) is one of the most promising sources of MSCs. However, the molecular and cellular characteristics of UC‐derived MSCs (UC‐MSCs) require extensive investigations, which are hampered by the limited lifespan and the diminished potency over passages. Here, we used the piggyBac transposon–based simian virus 40 T antigen (SV40T) immortalization system and effectively immortalized UC‐MSCs, yielding the iUC‐MSCs. A vast majority of the immortalized lines are positive for MSC markers but not for hematopoietic markers. The immortalization phenotype of the iUC‐MSCs can be effectively reversed by flippase recombinase–induced the removal of SV40T antigen. While possessing long‐term proliferation capability, the iUC‐MSCs are not tumorigenic in vivo. Upon bone morphogenetic protein 9 (BMP9) stimulation, the iUC‐MSC cells effectively differentiate into osteogenic, chondrogenic, and adipogenic lineages both in vitro and in vivo, which is indistinguishable from that of primary UC‐MSCs, indicating that the immortalized UC‐MSCs possess the characteristics similar to that of their primary counterparts and retain trilineage differentiation potential upon BMP9 stimulation. Therefore, the engineered iUC‐MSCs should be a valuable alternative cell source for studying UC‐MSC biology and their potential utilities in immunotherapies and regenerative medicine. Abstract : In this study, we sought to establish reversibly immortalized umbilical cord mesenchymal stem cells (eg, iUC‐MSCs) using a piggyBac transposon–based SV40 T antigen (SV40T) immortalization system. We showed that UC‐MSCs were effectively immortalized, which could be reversed by flippase recombinase. A vast majority of the resulting iUC‐MSCs expressed MSC markers and retained the ability to differentiate into osteogenic, chondrogenic, and adipogenic lineages upon BMP9 stimulation. Therefore, the engineered iUC‐MSCs should be a valuable cell source for studying UC‐MSC biology and the potential utilities of their cells in immunotherapies and regenerative medicine.